Frequency of Anemia in Early Umbilical Cord Clamping in Term Pregnancy Neonates - Farhana, .; Nazeer, Madiha; Zainab, . (Biological and Clinical Sciences Research Journal, 2025)
Placental transfusion during the first few minutes after birth provides the newborn with an additional 80–100 mL of blood, increasing blood and red cell volume, which helps prevent neonatal anemia. Early umbilical cord clamping (ECC), performed within 30 seconds of delivery, interrupts this natural transfusion and may lead to reduced hematocrit and iron stores in neonates. Objective: To determine the frequency of anemia in term pregnancy neonates undergoing early umbilical cord clamping and to evaluate its association with maternal and neonatal factors. Methodology: This cross-sectional descriptive study was conducted at the Department of Obstetrics and Gynaecology, Shaikh Zaid Women Hospital, SMBBMU Larkana, over six months (February–July 2020). A total of 121 term neonates were included using non-probability consecutive sampling. Early cord clamping was performed within 30 seconds of birth, and cord blood hematocrit was measured using an automated analyzer. Neonatal anemia was defined as a hematocrit <45%. Maternal demographic, obstetric, and clinical data were recorded. Data were analyzed using SPSS v26, with chi-square tests used to assess associations; p≤0.05 was considered significant. Results: The mean maternal age was 28.26 ± 5.64 years, and the mean gestational age was 38.21 ± 1.03 weeks. Among 121 neonates, 31 (25.6%) were anemic and 90 (74.4%) were non-anemic. Maternal age, gestational age, parity, booking status, obesity, hypertension, and previous postpartum hemorrhage were not significantly associated with anemia, while maternal diabetes mellitus showed a significant relationship (p=0.039). Conclusion: A considerable proportion of term neonates developed anemia following early cord clamping. Promoting delayed cord clamping may help reduce neonatal anemia and improve early hematologic outcomes.